COVID-19 slightly reduced family resilience, coping, and disaster preparedness in ISTIFAR’s Lombok study - Sriyono Sriyono; Hakim Zulkarnain; Jujuk Proboningsih; Kiki A. Kurnia (Jàmbá)
The study aimed to evaluate the longitudinal impact of ISTIFAR programme (Islamic-Based Training for Family Resilience) to the family state of coping, resilience and disaster preparedness on longitudinal observation. A quasi-experimental design was employed with pre- and post-test intervention group only. The sample size was 63 families that survived the earthquake, which sampled using purposive sampling. The sampling criteria were disaster survivor, head of household, Muslim and mentally healthy. The variable was pre- and post-observation of coping, family resilience and disaster preparedness, with confounding factor of stress. The interview performed by structured questionnaire. The data analysed with Mann–Whitney U test and ordinal regression (α 0.05). The result was a statistical difference between the observation of 6 months prior and follow-up but a slight decline in all variables mean. In detail, coping (p = 0.000), family resilience (p = 0.000) and the disaster preparedness (p = 0.023). There was no statistical correlation between the coping, family resilience and the disaster preparedness towards pandemic stress (p = 0.747). Islamic-Based Training for Family Resilience positively impact coping, resilience and disaster preparedness, albeit slight declines over 6 months, but no evident correlation with coronavirus disease 2019 (COVID-19) pandemic stress.